Awareness And Perception Of Healthcare Workers Towards Healthcare Transformation In Saudi Arabia: A Cross-Sectional Study (The Review of Diabetic Studies, 2025)
Background: The healthcare system in Saudi Arabia is in a major change process due to the National Transformation Program (NTP), as one of the initiatives of Vision 2030. It is essential to learn the awareness and perception of healthcare workers towards these reforms in order to implement it successfully.Aim: The research was conducted to determine the level of awareness, perception, and preparedness of healthcare professionals to the current healthcare transformation in Saudi Arabia.Method: 300 healthcare workers in the Makkah Health Cluster were purposively sampled, and a cross-sectional study was conducted. The surveys to be completed included the level of awareness, perceived benefits, difficulties, and participants' preparedness to apply the healthcare reforms. The data were analysed using descriptive statistics and Pearson's correlation analysis.Results: Most respondents were female (71.7 %) and Saudi citizens (87.3%), and nurses were the most prevalent professionals (50 %). There were many positive correlations between perception readiness and the implementation of readiness (r = 0.83) and between perception benefits and challenges (r = 0.66). Gender differences were also observed, with males scoring higher on perceived benefits and challenges.Conclusion: Saudi Arabian healthcare professionals were typically willing to engage in the change, but demographic factors such as gender and professional role influenced perceptions. These results underscore the importance of targeted training and communication initiatives to increase healthcare personnel's participation in the transformation process within the framework of Vision 2030.